Exploring the Orientation factors of Women Entrepreneurs: A Life Course Approach - Khan, Shabnam (International Journal of Psychosocial Rehabilitation, 2020)
Entrepreneurship is recognized as driving force of socio-economic development that is multifaceted endeavor influenced by the contextual, social, economic, government/institutional supporting factors.To promote the women entrepreneurial initiatives, this study is intended to explore the women entrepreneurial experiences in Pakistani context by using life course approach. To address this major apprehension, basic qualitative research methodology and Gioia methodology has been applied, semi-structured interviews conducted from the women entrepreneurs working at micro-enterprises. During the interviews and data analysis, it is inferred thatwomen entrepreneurs have wonderful entrepreneurial journey to be socially and financially independent and get the feeling of achievement and gratification. They started their own ventures due to need of economic, independent and success. Women entrepreneurs have to perform dual responsibilities, facing work-life conflicts and having limited access to knowledge, market and funding. To cope up the entrepreneurial challenges, women need sound family and social support with creative and innovative business practices.They didn’t get any government/institutional support irrespective of the nature, type, size and scale of the business. It is quite appreciable that society trends and perceptions have transformed revolutionary, women efforts are accepted and appreciated now. This study is an encouraging tool for other women entrepreneurs to participate in making Pakistan economically and socially Superior. Moreover, this study will facilitate policy makers to designs policy frameworks and programs in order to untap the resources.